Current practice and determinants of medication management in long-term care facilities - Chong Tze Wei; Marhanis Salihah Omar (Archives of Global Professionals, 2016)
Background: Medication management is a complex process which involves different phases including prescribing, transcribing, ordering, dispensing, supplying, administering, and storing. This study aimed to assess the medication adherence and its barriers among the residents in long-term care facilities to identify residents who are at risk for medication-related problem and resident`s beliefs toward medication. Methods: A prospective cross-sectional study was conducted in 24 long-term care facilities in Malaysia. The Chi-square test was performed to see any association between the adherence level and medication beliefs. Results: A total number of 185 residents were interviewed and majority of the residents were identified as highly adherent to their medication. There was a significant association found between duration of disease and medication adherence (P = 0.002). With regards to their belief toward medication, most of the residents had weak necessity scores (mean = 16.85, standard deviation [SD] = ±3.41) and strong concern scores (mean = 13.91. SD = ±2.684). There was a significant association between medication beliefs and medication adherence (P = 0.007), and a high number of residents were identified as at high risk for medication-related problems. Conclusion: Residents' risk for medication-related problems and their overall well-being should be emphasized and related actions should be taken to rectify the problems.